2023
DOI: 10.3389/fimmu.2023.1107437
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T cell enhancement in adults with cystic fibrosis receiving Elexacaftor/Tezacaftor/Ivacaftor therapy

Abstract: IntroductionCystic fibrosis (CF), especially CF lung disease, is characterized by chronic infection, immune dysfunction including impairment of regulatory T cells (Tregs) and an exaggerated inflammatory response. CF transmembrane conductance regulator (CFTR) modulators have shown to improve clinical outcomes in people with CF (PwCF) with a wide range of CFTR mutations. However, it remains unclear whether CFTR modulator therapy also affects CF-associated inflammation. We aimed to examine the effect of elexacaft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Our findings indicate that not only IL-8, but also three other CXC chemokines are downregulated in response to ETI, suggesting mainly a decline of neutrophilic inflammation. Overall, these results are in line with previous studies reporting a normalisation of circulating neutrophil counts [ 9 ], reduced neutrophil-associated systemic cytokines [ 12 , 13 ] and reduced inflammatory airway markers such as neutrophil elastase in pwCF receiving ETI [ 14 , 15 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings indicate that not only IL-8, but also three other CXC chemokines are downregulated in response to ETI, suggesting mainly a decline of neutrophilic inflammation. Overall, these results are in line with previous studies reporting a normalisation of circulating neutrophil counts [ 9 ], reduced neutrophil-associated systemic cytokines [ 12 , 13 ] and reduced inflammatory airway markers such as neutrophil elastase in pwCF receiving ETI [ 14 , 15 ].…”
Section: Discussionsupporting
confidence: 91%
“…Data from previous studies analysing the effects of mono and dual combination CFTR modulators on inflammatory markers in sputum and plasma from pwCF are inconsistent [ [5] , [6] , [7] , [8] ]. Recent studies have reported a normalisation of circulating neutrophil counts [ 9 ], improvements in monocyte/macrophage function [ 10 , 11 ], and reduction in airway and systemic proinflammatory cytokines [ [12] , [13] , [14] , [15] , [16] ] in pwCF receiving triple combination ETI. Overall, data on the immunological impact of CFTR modulator therapy are scarce and incomplete.…”
Section: Introductionmentioning
confidence: 99%
“…The hallmark of CF is chronic unremitting lung disease, a major cause of morbidity and mortality in CF patients. This condition is characterized by chronic infections, immune dysfunction, and dysregulated airway inflammatory responses, evidenced by decreased Treg cell activity and excessive inflammatory reactions [ 186 , 187 ]. Treg cells, especially CD4 + CD25 + Treg cells, play a crucial role in maintaining the balance between anti-inflammatory and pro-inflammatory mediators, thereby stabilizing the immune system [ 187 , 188 ].…”
Section: The Role Of Treg Cells In Human Lung Diseasesmentioning
confidence: 99%
“…Furthermore, highly effective CFTR modulators have been developed to improve the quality of life for patients with multiple CFTR mutations. Treatment with Elexacaftor/tezacaftor/ivacaftor (ELX/TEZ/IVA) has been shown to down-regulate blood levels of pro-inflammatory factors IL-6, IL-8 and IL-17A and up-regulate the percentages of Treg cells in CF patients [ 186 ]. ELX/TEZ/IVA, the first approved triple CFTR modulator therapy, effectively addresses inflammation and immune dysregulation caused by CFTR deficiency [ 194 ].…”
Section: The Role Of Treg Cells In Human Lung Diseasesmentioning
confidence: 99%
See 1 more Smart Citation